INTOLERANSI DAN RESISTENSI MASYARAKAT TERHADAP KEMAJEMUKAN: STUDI KASUS KERUKUNAN BERAGAMA DI KOTA BOGOR, JAWA BARAT - elma haryani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2019)
Kota Bogor yang dikenal sebagai kota penyangga Ibukota Indonesia berpenduduk dengan beragam kelompok agama, etnis, dan suku. Keberagamannya itu kerap menimbulkan konflik, seperti konflik penyegelan Gereja Kristen Indonesia (GKI) Yasmin, penutupan pesantren Ibn Mas’ud, kekerasan dalam acara saur on the road, kristenisasi masyarakat dan ragam kelompok agama yang memicu kekerasan. Kasus-kasus tersebut menjadikan kota Bogor mendapat label sebagai kota intoleran. Penelitian ini menggunakan pendekatan kualitatif. Dengan analisa the power of identity dan The function of social conflict tindakan intoleransi di kota Bogor diketahui sebabnya, yaitu karena pemahaman agama yang rigid dan statis, konflik biasanya dilakukan oleh sekelompok massa. Kota Bogor masih memiliki peluang menjadi kota kerukunan, dengan adanya desa model kerukunan Pabuaran, kegiatan peace train, dan peran Forum Kerukunan Umat Beragama (FKUB).Kata Kunci: Intoleransi, Keberagaman, Moderasi. The city of Bogor is known as the buffer city of the capital of Indonesia, inhabited by a variety of religious, race and ethnic groups. Its diversity often leads to conflicts, such as the conflicts of the Indonesian Christian Church (GKI) Yasmin, the closing of Ibn Mas’ud Pesantren, violence in the Sahur on the Road program (during Ramadan), Christianization of the community, and the variety of religious groups that trigger violence. These cases have made the city of Bogor labeled as an intolerant city. This study uses a qualitative approach, by analyzing the power of identity and the function of social conflict, the act of intolerance in the city of Bogor can be traced its roots, namely because of the rigid and static understanding of religion. Conflict is usually carried out by a group of masses. Bogor city still has the opportunity to became a city of harmony, with the existence of the Pabuaran harmony village model, peace train activities, and the role of the Forum for Religious Harmony (FKUB). Keywords: Intolerance, Diversity, Moderation.